LEARNING CITATION CONVENTIONS THROUGH TEACHING APPLICATION: FROM STUDENTS’ PERSPECTIVE - Nur Hidayah Mohd Sharif; Nur Hazwani Mohd Muhridza; Faizal Yamimi Mustaffa; Norhiza Ismail; Faruk Muhammad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Undergraduates’ writings are found to be deficient in the sense of citation conventions. This lacking engages students in an inadvertent plagiarism which causes them to have no academic integrity. Therefore, an effective intervention is required to address this problem. Teaching application is believed to be the best answer that would fit 21st-century teaching and learning. This study is conducted in Universiti Teknologi Malaysia (UTM). Since UTM uses APA citation conventions in their academic writing, this study developed an APA citation application (ACA). The application contains nine modules in which each consists of an instructional video, assessment, and questionnaire. Students need to complete the first module, as a prerequisite for unlocking the subsequent modules. The purpose of this study is to investigate the undergraduates’ perception of using ACA in helping them to use correct citation conventions in their academic writing. The respondents were 67 undergraduates from five Advanced Academic Writing classes. Findings suggest that students found ACA to be helpful for them to understand the correct way of writing citations and to apply the skills in their term paper writing. This study is believed to equip students with necessary citing skills when writing their Undergraduate Final Project which is a compulsory university exit requirement.